N-Acyl-Homoserine Lactone Inhibition of Rhizobial Growth Is Mediated by Two Quorum-Sensing Genes That Regulate Plasmid Transfer - Wilkinson, A. (American Society for Microbiology, 2002)
The growth of some strains of Rhizobium leguminosarum bv. viciae is inhibited by N-(3-hydroxy-7-cis tetradecenoyl)-l-homoserine lactone (3OH-C(14:1)-HSL), which was previously known as the small bacteriocin before its characterization as an N-acyl homoserine lactone (AHL). Tn5-induced mutants of R. leguminosarum bv. viciae resistant to 3OH-C(14:1)-HSL were isolated, and mutations in two genes were identified. These genes, bisR and triR, which both encode LuxR-type regulators required for plasmid transfer, were found downstream of an operon containing trb genes involved in the transfer of the symbiotic plasmid pRL1JI. The first gene in this operon is traI, which encodes an AHL synthase, and the trbBCDEJKLFGHI genes were found between traI and bisR. Mutations in bisR, triR, traI, or trbL blocked plasmid transfer. Using gene fusions, it was demonstrated that bisR regulates triR in response to the presence of 3OH-C(14:1)-HSL. In turn, triR is then required for the induction of the traI-trb operon required for plasmid transfer. bisR also represses expression of cinI, which is chromosomally located and determines the level of production of 3OH-C(14:1)-HSL. The cloned bisR and triR genes conferred 3OH-C(14:1)-HSL sensitivity to strains of R. leguminosarum bv. viciae normally resistant to this AHL. Furthermore, bisR and triR made Agrobacterium tumefaciens sensitive to R. leguminosarum bv. viciae strains producing 3OH-C(14:1)-HSL. Analysis of patterns of growth inhibition using mutant strains and synthetic AHLs revealed that maximal growth inhibition required, in addition to 3OH-C(14:1)-HSL, the presence of other AHLs such as N-octanoyl-l-homoserine lactone and/or N-(3-oxo-octanoyl)-l-homoserine lactone. In an attempt to identify the causes of growth inhibition, a strain of R. leguminosarum bv. viciae carrying cloned bisR and triR was treated with an AHL extract containing 3OH-C(14:1)-HSL. N-terminal sequencing of induced proteins revealed one with significant similarity to the protein translation factor Ef-Ts.